Fudging the Numbers: Understanding the Politics and Dynamics of Population Census Figures in Nigeria - Ota, Ejitu N.; Ndubuisi, Uchechukwu (Kashere Journal of Politics and International Relations, 2025)
The Policymakers use population census as a reference for efficient social mobilisation, economic planning, and overall national development. However, its manipulation and politicisation have the negative impact of inadequate planning, which obstructs actual advancement. Ascertaining Nigeria's population has been a complex endeavour with its controversies since 1866, and as such has been based on conjectures rather than precise enumeration and valid data presentation. This study employed a qualitative research methodology, thus highlighting the controversies surrounding Nigeria’s census exercise over years and how this affects economic and development planning. The study made the case that the British colonial government intentionally favoured the then Northern region throughout Nigeria's history of population census manipulation for ostensibly ulterior purposes. It discovered that since the North has held political power for over thirty of Nigeria's sixty-four years of independence, successive federal governments that were, in a sense, controlled by Northerners have persisted in politicising and even weaponizing head counting in the country. The paper concluded that the manipulation and politicisation of population census figures in favour of the North vis-à-vis the South is a major impediment to national integration and development.